Novel Potassium-Competitive Acid Blocker, Tegoprazan, Protects Against Colitis by Improving Gut Barrier Function - Son, Mijeong; Park, I Seul; Kim, Soochan; Ma, Hyun Woo; Kim, Ji Hyung; Kim, Tae Il; Kim, Won Ho; Han, Jaeyong; Kim, Seung Won; Cheon, Jae Hee (Frontiers in Immunology, 2022)
Inflammatory bowel disease (IBD) is a chronic immune-mediated disorder characterized by prolonged inflammation of the gastrointestinal tract. IBD can result from gut barrier dysfunction, altered gut microbiota, and abnormal intestinal immunity induced by environmental factors in genetically susceptible individuals. Proton pump inhibitors (PPIs) such as rabeprazole are frequently employed for gastric acid inhibition. However, long-term PPI administration can alter the intestinal microbiome composition, possibly worsening IBD severity. The present study revealed that tegoprazan, a potassium-competitive acid blocker, significantly improved colitis in mice and enhanced the intestinal epithelial barrier function. Tegoprazan alleviated gut microbiota dysbiosis and enhanced the growth of Bacteroides vulgatus. In turn, B. vulgatus alleviated intestinal inflammation by inhibiting epithelial adhesion of pathogenic bacteria. Unlike rabeprazole, tegoprazan did not induce gut dysbiosis. Our findings provide novel insights into the potential role of tegoprazan as an intestinal protectant for IBD and as a therapeutic agent for gastric acid-related diseases.